Prospects for a pharmacoinvasive strategy in ST-elevation myocardial infarction in the Russian Federation - V. E. Oleynikov; R. M. Shakhnovich; A. N. Yakovlev; R. M. Rabinovich; I. V. Avdeeva (Российский кардиологический журнал, 2025)
In patients with ST-elevation myocardial infarction, primary percutaneous coronary intervention should be performed within 120 minutes after diagnosis if possible. Timely revascularization helps to preserve left ventricular function, minimizing myocardial damage, which subsequently reduces disability and mortality. There are patients for whom this approach cannot be implemented within the specified time frame for a number of reasons. In such a situation, a pharmacoinvasive strategy is recommended, which involves thrombolytic therapy as the first stage. Current treatment strategies for myocardial infarction have been compared many times. An undoubted advantage in Russia is the availability of domestic staphylokinase agent, which has a good efficacy and safety profile, meeting the requirements for fibrin specificity. Thus, research determining the current place of pharmacoinvasive strategy should be continued to optimize thrombolysis and improve the prognosis in patients with myocardial infarction.